The Global Plastics Treaty: An Endocrinologist's Assessment - Fernandez, Marina Olga (2024)
Plastics are everywhere. They are in many goods that we use every day. However, they are also a source of pollution. In 2022, at the resumed fifth session of the United Nations Environment Assembly, a historic resolution was adopted with the aim of convening an Intergovernmental Negotiating Committee to develop an international legally binding instrument on plastic pollution, including in the marine environment, with the intention to focus on the entire life cycle of plastics. Plastics, in essence, are composed of chemicals. According to a recent report from the secretariat of the Basel, Rotterdam, and Stockholm conventions, around 13 000 chemicals are associated with plastics and plastic pollution. Many of these chemicals are endocrine-disrupting chemicals and, according to reports by members of the Endocrine Society and others, exposure to some of these chemicals causes enormous costs due to the development of preventable diseases. The global plastics treaty brings the opportunity for harmonized, international regulation of chemicals with endocrine disrupting properties present in plastic products.